Attagenus larva in the sinus cavity in a patient with complications after the use of hyaluronic acid filler - Zuzanna Swierczewska; Wioletta Baranska-Rybak (Surgical & Cosmetic Dermatology, 2022)
A wide range of dermal fillers is now available for use in the beauty industry. We present a case of a 33-year-old woman with complications after hyaluronic acid injection by a non-medical practitioner. Two weeks after the injection, bilateral sinus pain, fever, and burning sensation occurred in the cheek area. She underwent a detailed diagnosis revealing Attagenus larva in the paranasal sinus. Despite treatment, the symptoms remained. Thus, hyaluronidase was administered in the infraorbital area, obtaining a full remission.